Some Early Definitions of Taṣawwuf: Exploring the Centrality of Abū Yazīd al-Bisṭāmi in Its History - Mohamed Meerasahibu, Dheen Mohamed (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
The purpose of this article is to present some early definitions of taṣawwuf, uttered by a Sufi who lived before the end of the first half of the third/ninth century known by his paidonymic Abū Yazīd al-Bistāmī (161AH–234AH). The importance of this discussion – which employs the historical analytical method – stems from the fact that the definitions under study reflect a highly developed Sufi experience. The paper concludes that Abū Yazīd’s definitions are among the earliest known to us and that taṣawwuf had reached its maturity well before the end of the first half of the third century AH. This would I feel prompt researchers in the field to reassess and reconstruct the history of taṣawwuf, especially in its formative period, and might well lead to a new narrative of its development.